2016
DOI: 10.1002/app.44445
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and anti‐corrosion behaviors of water dispersible graphene/acrylic modified alkyd resin latex composites coated carbon steel

Abstract: A type of water dispersible graphene (PG) has been synthesized by nucleophilic ring‐opening reaction of the primary amine group in 3‐(1‐(2‐aminopropoxy) propan‐2‐ylamino) propane‐1‐sulfonate sodium (PPS) with epoxy groups on the basal plane of graphene oxide (GO), followed by in situ reduction with hydrazine hydrate. The PG is employed as nanoscale reinforcement fillers in waterborne acrylic modified alkyd resin (AMAR) coatings. The stability and corrosion resistance of the waterborne PG/AMAR nanocomposite coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 52 publications
(57 reference statements)
1
16
0
Order By: Relevance
“…22,23 Further investigation would be needed to explore the mechanism in detail. In this work, comparing the results with other studies reported in the literature, 13 it was found that MPS grafting onto the GO surface was able to decrease the settling velocity of the GO suspension and GO spatial distributions might have a great significance for the suspension stability. As a result, MPS was chosen as a chemical modified additive since it played an important role in subsequent interfacial interaction on the surface of UFP and graphene oxide.…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations
“…22,23 Further investigation would be needed to explore the mechanism in detail. In this work, comparing the results with other studies reported in the literature, 13 it was found that MPS grafting onto the GO surface was able to decrease the settling velocity of the GO suspension and GO spatial distributions might have a great significance for the suspension stability. As a result, MPS was chosen as a chemical modified additive since it played an important role in subsequent interfacial interaction on the surface of UFP and graphene oxide.…”
Section: Resultssupporting
confidence: 63%
“…In this work, increasing GO content to 2% had a significant effect on accelerating the corrosion rate of the MGO/UFP composite coatings because of poor film-forming ability, hard dispersion property of GO and weak adhesion to the metallic substrate. 13,15…”
Section: Potentiodynamic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The Bode plots, exhibit high frequency region due to the coating capacitance and low frequency region due to charge transfer processes occurring at solution/coating interface. Since presenting electrochemical impedance spectroscopy results by Nyquist and Bode plots are a common way for exploring the corrosion resistance of coating systems [44][45][46][47], these plots are presented and discussed in this research. 6 and 7 show the Bode and Nyquist diagrams of mild steel substrate coated with pure epoxy and epoxy/AF g-C 3 N 4 coatings after immersion in 3.5 wt% NaCl solution for 2 h, 24 h, and 48 h, respectively.…”
Section: Corrosion Protection Performance Of Epoxy/af G-c 3 N 4 Nanocmentioning
confidence: 99%